Enhanced External Counterpulsation Is an Effective Treatment for Depression in Patients With Refractory Angina Pectoris - May, Ole (Prim Care Companion CNS Disord, 2015)
OBJECTIVE: To examine the effect of enhanced external counterpulsation (EECP) on depression in patients with refractory angina pectoris (Canadian Cardiovascular Society class 2–4). METHOD: The study was a prospective observational investigation with a 2-month control period preceding the EECP therapy (to minimize a possible effect of the regression-toward-the-mean phenomenon). The patients were examined 2 months before and just before EECP and just after, 3 months after, and 12 months after EECP. Depression was assessed using the Major Depression Inventory and the ICD-10. During EECP, 3 sets of cuffs were fastened around the lower extremities and were inflated sequentially to a pressure of 260 mm Hg in each diastole for 60 minutes 5 days a week for 7 weeks (35 sessions). The study was conducted at a regional hospital in Denmark from May 2006 to January 2011. RESULTS: Fifty patients with angina pectoris and an abnormal coronary angiography, with no possibility for revascularization, were included (72% men, mean age of 63 years) between May 2006 and January 2011. The prevalence of depression before EECP was 18%, just after was 2%, 3 months after was 2%, and 12 months after was 4% (P = .013). The depressive state was more severe at a lower age (P = .016). No significant predictors of effect of EECP on depression were found (P > .05), and no association was detected between decline in depressive state and chest pain (P > .05). CONCLUSIONS: The study indicates that EECP is an effective treatment for depression in patients with refractory angina pectoris, that depression is more severe in younger patients, and that the effect of EECP on depression is not related to the effect on chest pain. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT01112163